Discovery of high and very high-energy emission from the BL Lacertae object SHBL J001355.9-185406 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A.G.; Angüner, E.; Anton, G.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker Tjus, J.; Bernlöhr, K.; et al. (Astronomy and astrophysics., 2013)
The detection of the high-frequency peaked BL Lac object (HBL) SHBL J001355.9–185406 (z = 0.095) at high (HE; 100 MeV < E < 300 GeV) and very high-energy (VHE; E > 100 GeV) with the Fermi Large Area Telescope (LAT) and the High Energy Stereoscopic System (H.E.S.S.) is reported. Dedicated observations were performed with the H.E.S.S. telescopes, leading to a detection at the 5.5σ significance level. The measured flux above 310 GeV is (8.3 ± 1.7stat ± 1.7sys) × 10-13 photons cm-2 s-1 (about 0.6% of that of the Crab Nebula), and the power-law spectrum has a photon index of Γ = 3.4 ± 0.5stat ± 0.2sys. Using 3.5 years of publicly available Fermi-LAT data, a faint counterpart has been detected in the LAT data at the 5.5σ significance level, with an integrated flux above 300 MeV of (9.3 ± 3.4stat ± 0.8sys) × 10-10 photons cm-2 s-1 and a photon index of Γ = 1.96 ± 0.20stat ± 0.08sys. X-ray observations with Swift-XRT allow the synchrotron peak energy in νFν representation to be located at 1.0 keV. The broadband spectral energy distribution is modelled with a one-zone synchrotronself-Compton (SSC) model and the optical data by a black-body emission describing the thermal emission of the host galaxy. The derived parameters are typical of HBLs detected at VHE, with a particle-dominated jet.
EPrint Processing Status: Full text deposited in DRO
Keywords: BL Lacertae objects: individual: SHBL J001355.9-185406; Gamma rays: general.